Optimization of Incubation Time and Coagulant Concentration of Ficus carica L. Latex for Fresh Goat Cheese Production - Nugraha, Widitya Tri; Murti, Tridjoko Wisnu; Erwanto, Yuny; Nurliyani, Nurliyani; Suranindyah, Yustina Yuni; Muhlisin, Muhlisin; Fibri, Dwi Larasatie Nur (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
Cheese coagulants from plant origin have emerged as promising alternatives to animal rennet in cheese production. Among them, latex from Ficus carica L. has shown potential as a natural milk-clotting agent for goat cheese production. This study aims to determine the optimal incubation time and fig tree latex extract concentration on the quality of goat cheese. The optimization of the production process of the goat cheese was carried out using Response Surface Methodology (RSM) with Central Composite Design (CCD). The independent variables were the concentration of the Ficus carica L. latex extract (0.2-0.5 mL/100 mL of milk) and the time of incubation (60-120 min). The goal was to achieve maximum protein content (%), ash content (%), and calcium content (%). The results of this study showed that the Ficus carica L. latex extract used in the study could coagulate milk with a strength of 354.69 MCU and a dominant protein molecular weight of about 20 kDa. The optimization results using RSM method with CCD design showed that the goat cheese was produced optimally in 0.5 mL/100 mL of milk for the concentration of Ficus carica L. latex extract, with 120 min incubation time. These optimal conditions resulted in a cheese with protein content of 18.56%, ash content of 2.32%, calcium content of 803.93 mg/100g, and desirability level of 0.93.